Case report: Pediatric intraventricular Rosai-Dorfman disease: clinical insights and surgical strategies in a decade-long observational study and literature review - Liu, Dayuan; Li, Ning; Zhu, Yubo; Zhong, Yunxiang; Deng, Guolong; Wang, Mingfa; Zhang, Caicai; Feng, Jigao (Frontiers in Oncology, 2024)
BackgroundRosai-Dorfman disease (RDD), or sinus histiocytosis with massive lymphadenopathy (SHML), is a rare benign disorder characterized by the proliferation of histiocytes of uncertain origin. Central nervous system (CNS) involvement, particularly intraventricular, is exceptionally rare and poses significant diagnostic challenges due to its non-specific clinical and radiographic presentation. This study aims to present a case of intraventricular RDD and review existing literature on its clinical features, treatment strategies, and prognosis.MethodsWe report the case of a five-year-old male with recurrent headaches and epilepsy caused by an intraventricular mass. The mass was surgically resected and histopathological examination was performed to confirm the diagnosis. A comprehensive literature review was conducted to identify similar cases of intraventricular RDD, focusing on clinical features, diagnostic methods, treatment strategies, and outcomes.ResultsHistopathological examination of the resected tumor revealed typical features of RDD, including large histiocytes, lymphocyte infiltration, and immunohistochemical positivity for CD68, S-100, and Vimentin. The patient remained asymptomatic ten years post-surgery with no recurrence of epilepsy or tumor. The literature review identified six similar cases, all of which showed favorable outcomes post-surgery, highlighting the self-limiting nature and favorable prognosis of intraventricular RDD following surgical resection.ConclusionIntraventricular RDD, though rare, should be considered in the differential diagnosis of intraventricular masses in pediatric patients. Surgical resection remains the primary treatment modality, and histopathological confirmation is essential for accurate diagnosis. The prognosis is generally favorable with appropriate surgical intervention, although recurrence can occur, necessitating long-term follow-up. Further research is required to refine diagnostic criteria and explore adjuvant therapies for improved management of this rare CNS disorder.